2009
DOI: 10.1126/science.1174012
|View full text |Cite
|
Sign up to set email alerts
|

A Constant Flux of Diverse Thermophilic Bacteria into the Cold Arctic Seabed

Abstract: Microorganisms have been repeatedly discovered in environments that do not support their metabolic activity. Identifying and quantifying these misplaced organisms can reveal dispersal mechanisms that shape natural microbial diversity. Using endospore germination experiments, we estimated a stable supply of thermophilic bacteria into permanently cold Arctic marine sediment at a rate exceeding 10(8) spores per square meter per year. These metabolically and phylogenetically diverse Firmicutes show no detectable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
222
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(250 citation statements)
references
References 24 publications
28
222
0
Order By: Relevance
“…The determined optimum temperature is significantly higher than the reported in situ temperature at cold seeps and gas hydrates (4-8 1C; Suess et al, 1999;Orcutt et al, 2004). Similar findings have been reported in previous studies (Isaksen and Jørgensen, 1996;Finke and Jørgensen, 2008;Hubert et al, 2009). It was commonly observed that microorganisms living in arctic environments displayed optimum growth or respiration rates at temperatures significantly higher than those encountered in situ, whereas microorganisms from hot environments exhibit optimum temperatures closer to the actual in situ temperatures (Stetter et al, 1990;Jørgensen et al, 1992).…”
Section: Resultssupporting
confidence: 66%
“…The determined optimum temperature is significantly higher than the reported in situ temperature at cold seeps and gas hydrates (4-8 1C; Suess et al, 1999;Orcutt et al, 2004). Similar findings have been reported in previous studies (Isaksen and Jørgensen, 1996;Finke and Jørgensen, 2008;Hubert et al, 2009). It was commonly observed that microorganisms living in arctic environments displayed optimum growth or respiration rates at temperatures significantly higher than those encountered in situ, whereas microorganisms from hot environments exhibit optimum temperatures closer to the actual in situ temperatures (Stetter et al, 1990;Jørgensen et al, 1992).…”
Section: Resultssupporting
confidence: 66%
“…The present study also raises the question of whether microbes in extreme environments are actually functioning there or are being constantly deposited from elsewhere (and thus end up being found in clone libraries and culturing efforts even if they cannot function in those environments [42]). At present, this remains an open question for soils of both the high Himalayas and the Dry Valleys of Antarctica, but there is accumulating evidence that photoautotrophs and chemoautotrophs can function in similar extreme soils of the high Andes and Rocky Mountains [4,14,43].…”
Section: Resultsmentioning
confidence: 99%
“…Peter et al 2014), and dormancy allows for persistence within less than favorable habitats (e.g. Hubert et al 2009). Thus, microbial mechanisms for dispersal and dormancy may allow microorganisms adapted to disparate habitats to coexist.…”
Section: Local Rarity Along Habitat Gradients Linked By Regional Metamentioning
confidence: 99%